Gastronomy and hospitality studies in tourism - Isin, Alper; Yayla, Ozgur; Yazicioglu, Irfan (Peter Lang, 2021)
"This book includes studies carried out with a scientific purpose in gastronomy and hospitality in tourism and aims to provide theoretical and practical contributions to both academicians and sector employees. In line with this purpose, the importanceand awareness of in tourism, especially gastronomy and food, is revealed, so it is possible to associate conceptual studies with other areas of tourism. In addition, the content has been enriched with examples of hospitality applications in tourism"-- Provided by publisher